Inducing ferromagnetism in surface stabilised intrinsic CdSe nanoparticles by a simple process. Issue 13 (1st September 2020) - Pokhriyal, Sumit; Biswas, Somnath
Abstract : In this letter, we report a simple process to derive in situ surface stabilised intrinsic CdSe nanoparticles (NPs) showing room temperature ferromagnetism (RTFM). The observed RTFM is primarily attributed to the lattice strain ( ε ) in the NPs supported by an effective core (CdSe)-shell (surface layer) charge transfer mechanism. The synthesis method allows precise control over particle morphology and dispersity, and is highly convenient in tuning the magnetic properties for pertinent applications. Highlights Magnetic CdSe nanoparticles were synthesized by a facile process. In situ formed graphitic-carbon layer on the surface stabilises the nanoparticles. The process permits precise control over particle morphology and dispersity. The technique is also convenient in tuning the magnetic properties. Monodispersed magnetic CdSe nanoparticles have potential applications in modern optoelectronics. GRAPHICAL ABSTRACT: